Internal migration in Brazil: exploring migration of high-skilled workers towards economic complex locations - de Oliveira, Heder Carlos; Balemans, Tim; Lima, Ana Carolina da Cruz (Revista Econômica do Nordeste, 2021)
This paper researches the determinants for internal migration in Brazil towards economic complex cities using logit estimates on data of the Brazilian Census in 2010. It contributes to existing literature in the way that it combines internal migration patterns with economic complexity. The most important findings of this paper are twofold. Firstly, people who already lived in an economic complex city in 2005 had a higher probability of migrating to another economic complex city in 2010 than people who did not live in an economic complex city in 2005. Secondly, low-skilled workers have a lower probability of migrating to an economic complex city than high-skilled workers, which is in line with the expectations. Studying internal migration patterns is of importance as national and regional policymakers could get more understanding of the internal migration patterns towards economic complex locations and use the findings of this paper to steer internal migration in Brazil.